Pedagogical practices of overcoming personal fragility and social limitations in Ukrainian students during the war - Sysoieva, Svitlana; Lytovchenko, Olena; Kunytsia, Tetiana (Kultura-Społeczeństwo-Edukacja, 2025)
The article is devoted to the problem of overcoming personal fragility and social limitations among students during the war in Ukraine. The notion of “fragility” has become highly relevant in the global dimension in an era of numerous crises, shocks, and uncertainty. According to the OECD report ‘States of Fragility 2025’, fragility is defined as a combination of increased risks and insufficient response capacities of states, systems, and/or communities to manage, absorb, or mitigate such risks. The current situation of the Russian-Ukrainian war fully corresponds to its thesis of “living with fragility and responding to it”. The article presents research findings confirming the crucial role of extracurricular education in this context. Institutions of extracurricular education in Ukraine implement educational programs, social and creative projects, forums, competitions, and volunteer initiatives; they also provide social rehabilitation and psychosocial support, particularly for children affected by war, children from internally displaced families, and those with learning difficulties. Special relevance is accorded to socio-pedagogical practices of overcoming fragility and fostering resilience among students under risks and threats.